S12.1 Il-16 – a urinary biomarker for proliferative lupus nephritis. (27th September 2022) - Häyry, A; Faustini, F; Zickert, A; Larsson, A; Sundelin, B; Svenungsson, E; Oke, V; Gunnarsson, I
Abstract : Background: Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus (SLE). The pathogenesis is incompletely understood and good biomarkers for non-invasive diagnostics are scarce. Interleukin (IL)-16 is an immunomodulatory cytokine with an emerging role in SLE and LN. 1–4 Aim: To investigate IL-16 as a potential biomarker for LN in a well-characterized cohort of SLE patients. Methods: We measured urinary and plasma IL-16 levels in predefined patient groups: active LN (n=84), active non-renal SLE (n=63), inactive non-renal SLE (n=73) and in matched population controls (n=48) using ELISA. The LN group included patients with proliferative (PLN, n=47), mesangioproliferative (MES, n=11), and membranous (MLN, n=26) LN. Renal expression of IL-16 was investigated by immunohistochemistry (IHC). Associations between IL-16 and clinical variables and the diagnostic value of IL-16 levels for LN were explored. Results: Urinary IL-16 levels were highest among patients with LN (p<0.0001), particularly among those with PLN (p<0.035). High plasma IL-16 levels were observed in patients with active SLE, both in active renal and non-renal groups (p<0.01). In PLN, urinary IL-16 levels correlated to renal activity index (ρ=0.39, p=0.007), and albuminuria (ρ=0.31, p=0.034). IL-16 was expressed in a high proportion of cells in renal inflammatory infiltrates. In the regression models, urinary IL-16 discriminated PLN cases from all other investigated cases in the cohort (AUC=0.797, p=0.001) and other LN patients (AUC 0.775, p=0.001), while plasma IL-16 did not. Detectable urinary IL-16 had superior specificity but lower sensitivity than elevated dsDNA, low C3 or C4 for diagnosing PLN both among the whole cohort and among LN patients. Conclusions: Our data suggest that urinary IL-16 can non-invasively discriminate patients with proliferative lupus nephritis from other SLE patients. Furthermore, the abundance of IL-16 in urine and presence in kidney tissue imply a role in the pathogenesis of lupus nephritis. Its potential as a therapeutic target in SLE should be explored. References: Idborg, H. et al . TNF-α and plasma albumin as biomarkers of disease activity in systemic lupus erythematosus. Lupus Sci Med 2018. Niewold, T. B. et al . Proteome study of cutaneous lupus erythematosus (CLE) and dermatomyositis skin lesions reveals IL-16 is differentially upregulated in CLE. Arthritis Res Ther 2021. Xue, H. et al . The IL-16 gene polymorphisms and the risk of the systemic lupus erythematosus. Clin Chim Acta 2009. Fava, A. et al . Urine Proteomics and Renal Single Cell Transcriptomics Implicate IL-16 in Lupus Nephritis. Arthritis Rheumatol 2021